THE USE OF NILE TILAPIA SKIN XENOGRAFTS IN THE TREATMENT OF TRAUMA CAUSED BY BURNS (CIPEEX, 2025)
Every year, approximately one million people suffer burns in Brazil. These injuries are caused by exposure to a variety of sources, causing pain, loss of tissue function and increased hospitalization costs. The best dressing for this type of trauma is one that alleviates pain and, most importantly, prevents contamination, prevents hydroelectrolytic losses and promotes epithelialization. Using skin grafts is the first option for deep burns. In the private sector, there is the possibility of using biosynthetic dressings or artificial skins, which have great benefits, but are not yet a reality for the public service. To overcome this obstacle, new alternatives are being developed, including the use of Nile Tilapia skin. This production highlights the importance of new methods for the treatment of superficial and deep burns. This study aims to verify whether the use of Nile tilapia skin xenografts provides better options as a treatment for burns. This is an integrative literature review, with articles obtained through searches in the SciELO and PubMed databases with their respective descriptors in Health Sciences - DeCS: Burns; Tilapia; Skin, with the Boolean operator AND. Original and complete articles produced between 2019 and 2024 were included. Articles that were not related to the research objective were excluded, and 9 were selected in the end. Burns are traumas that affect a large part of the population every year, and treatment is expensive or not available in all regions. As an alternative to conventional treatment, Nile tilapia skin has twice as much type I collagen as human skin, which stimulates fibroblast growth factors (FGFs), which express and release keratinocyte growth factor (KGF), two important cytokines that are essential for wound closure. These xenograft dressings have good tensile and compression resistance and keep the wound moist. In addition, these biological dressings prevent contamination by avoiding hydroelectrolytic losses and by adhering well to the wound. Furthermore, the lack of need for daily changes of the xenograft resulted in less pain than in patients treated with 1% silver sulfadiazine occlusive dressing. This also reduces team work and hospital costs. It is concluded that the Nile tilapia xenograft showed a good response as an occlusive biological dressing, presenting good adhesion to the wound bed, without hematological alterations, with promising results and high excellence in the treatment of burns. In addition, this material presents a low-cost alternative to reduce healing time and reduce pain and physical and mental discomfort of burn patients.
Keywords: tilapia; burns; skin; bandages